Signet ring cell percentage in poorly cohesive gastric cancer patients: A potential novel predictor of survival. Issue 3 (March 2022) - Roviello, Franco; Marano, Luigi; Ambrosio, Maria Raffaella; Resca, Luca; D'Ignazio, Alessia; Petrelli, Federica; Petrioli, Roberto; Costantini, Maurizio; Polom, Karol; Macchiarelli, Raffaele; Biviano, Ivano; Marrelli, Daniele
Abstract: Background and objectives: Signet ring cells (SRC) are widely acknowledged as a prognostically unfavorable histotype amongst poorly cohesive gastric cancer. In this study we evaluated the impact of SRC percentage on the clinical, pathological and prognostic features of these tumors according to the classification by the European Chapter of the IGCA. Methods: We retrospectively reviewed records of patients with poorly cohesive gastric cancer that underwent surgery between 1995 and 2016, whose tissue specimens were available in a biological bank. All slides were put under revision, patients were reclassified into three groups according to the proportion of signet ring cells: "pure" SRC (containing ≥90% of SRCs), Poorly Cohesive-Not Otherwise Specified (PC–NOS) (containing ≤10% of SRCs), and PC-NOS/SRC (containing <90% but >10% of SRCs). The clinicopathological factors between different types were analyzed and prognostic differences were compared. Results: Among 143 enrolled patients, 51% were male and 49% were female. The mean (±SD) age at diagnosis was 61 ± 13.9 years. Eighty-seven patients (60.8%) were reclassified as PC-NOS, 56 (39.2%) as PC-NOS/SRC and none as "pure" SRC. Five-years overall survival was significantly higher in PC-NOS/SRC group (63.3%) compared with PC-NOS group (12.7%). The increase in mortality risk was more than four-fold in patients with PC-NOS pattern compared to those with PC-NOS/SRC (HR 4.32 [95% CI 2.5–7.4]. After adjustment for potential confounding factors, SRC pattern was still an independent predictor of survival. Conclusions: The percentage of SRCs is inversely related to tumor aggressiveness, confirming the role of SRC pattern as an independent predictor of survival.